The Effectiveness of Multimedia-Based Blended Learning Method for Analysis of the Concept Understanding and Characters Development of Students in Hydrocarbon Compound Subject Matter (Universitas Negeri Semarang, 2020)
The development of communication and information technology has become an opportunity in the development of learning. Conventional learning is no longer effective in improving student learning outcomes. So it is important to apply technology integration as a medium and resources in a blended learning system. This study aims to measure how effective the application of blended learning in improving the learning outcomes in hydrocarbon compound. Using quantitative methods, this research is experimental research. The research object was divided into control class and experimental class, data mining was carried out with test and questionnaire. The analysis technique uses N-Gain Score and One-sample T-Test with counting technique assisted by IBM SPSS Statistics 22. The results showed that the application of blended learning to increase students' conceptual understanding in the category of